Bioecological characteristics of modern soil cover in subtropic regions of Azerbaijan - Verdiyeva Bahram, Farida; Allahverdi, Turkan Hasanova; Eyvaz, Mahsati Ismayilova; Yusif, Elnur Huseynov; Jabiyeva Elshad, Telli; Asgarova Farhad, Gunel (Institute of Advanced Engineering and Science, 2025)
The purpose of this study is to introduce innovation in the field of agriculture in Azerbaijan by determining the abundance of various ecotrophic groups of microorganisms (involved in the formation and mineralization of humic substances) in natural and cultivated gray-brown soils. Studying the microbiological indicators of humic substance transformation in virgin soils and determining the direction of these processes under the influence of anthropogenic factors in agrocenoses soils is considered relevant for the development of the agricultural sector in the Lankaran region. It was found that perennial woody vegetation increased the abundance of pedotrophic microorganisms by 17-21% and humate decomposers by 12-14% compared to completely natural soil. The correlation coefficient between the abundance of humate decomposers and the pedotrophic index was r=-0.685±0.09. Plowing natural gray-brown soils reduces the total humus content and the abundance of micromycetes, which form the peripheral portion of humic substances.